Challenges of Online Education among University Students, Saudi Arabia - Lizy Sonia Benjamin; B. Joshua Steve Abishek; Yulis Setiya Dewi; Priya Sivaram; Yoyok Bekti Prasetyo (Jurnal Ners, 2021)
Introduction: Online education during COVID 19 pandemic is witnessing significant growth, particularly in higher education. The aim of the study will explore the challenges that are being encountered related to online education for nursing students.Methods: A correlational study using cross-sectional approach was adopted among 150 participants selected through convenient sampling technique. Data was collected through electronic survey from undergraduate students participated voluntarily studying in College of Nursing, King Khalid University, Abha, Saudi Arabia. The survey forms (Rating Scales on satisfaction and barriers of online education) were used to collect the data. Descriptive and inferential statistics were used to analyze the data by using SPSS version 24.0.Results: The results revealed nearly 92% of participants were highly satisfied with online education. The mean scores and SD related to satisfaction of online education was (37.50+ 8.50). The global perceived barriers mean scores and SD were (35.19+11.19) which indicates that they were able to quickly adopt new strategies by overcoming the limitations.Conclusion: The researcher concludes with the fact that study findings support that, students had positive perception on benefits of online learning by overcoming the limitations. In conclusion, online teaching and learning can be effectively incorporated in future also using blended approach.